PENGARUH PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI ALFAMIDI SUDIRMAN TELUKDALAM KABUPATEN NIAS SELATAN - Khodasokhi Duha (Universitas Nias Raya, 2023)
mentioned in this study. So it can be concluded that promotional activities can have a significant influence on purchasing decisions at Alfamidi Sudirman Telukdalam South Nias Regency. The suggestions given are based on the research results, namely: 1) Alfamidi Sudirman Telukdalam South Nias Regency should do more promotional activities than what has been done in order to attract more consumers and make purchasing decisions. 2) Alfamidi Sudirman Telukdalam South Nias Regency should pay attention to other things that influence purchasing decisions, for examples the difference between the price on the shelf and at the cashier.